2013
DOI: 10.1017/s0007114512006046
|View full text |Cite
|
Sign up to set email alerts
|

Association between self-reported sleep duration and dietary quality in European adolescents

Abstract: Evidence has grown supporting the role for short sleep duration as an independent risk factor for weight gain and obesity. The purpose of the present study was to examine the relationship between sleep duration and dietary quality in European adolescents. The sample consisted of 1522 adolescents (aged 12.5-17.5 years) participating in the European multi-centre cross-sectional ‘Healthy Lifestyle in Europe by Nutrition in Adolescence’ study. Sleep duration was estimated by a self-reported questionnaire. Dietary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
44
2
8

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(59 citation statements)
references
References 55 publications
5
44
2
8
Order By: Relevance
“…Low moderate-to-vigorous PA and sedentary lifestyle are common in obese subjects [17,34,35]. In the present study, time spent in supervised PA was repeatedly lower in the obese subjects compared with controls.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…Low moderate-to-vigorous PA and sedentary lifestyle are common in obese subjects [17,34,35]. In the present study, time spent in supervised PA was repeatedly lower in the obese subjects compared with controls.…”
Section: Discussionsupporting
confidence: 49%
“…Several unhealthy lifestyle factors are associated with increased weight and overweight, including shorter sleep duration, increased stress level, poor dietary quality, and smoking [17,35]. The two latter factors were marked in the present study: smoking was more common in obese subjects, and HEI, mirroring dietary quality, was lower than in normal-weight controls.…”
Section: Discussionsupporting
confidence: 43%
“…Likewise, epidemiologic studies are generally consistent in showing that short sleep duration is associated with higher caloric consumption and poorer dietary quality [48][49][50]. We also recently reported that short sleep duration (≤6 h per night) was associated with greater alcohol consumption and an increased risk of exceeding the guidelines for sensible weekly alcohol intake in adults [51].…”
Section: Insufficient Sleep and Energy Intakementioning
confidence: 60%
“…e Includes 58 cross-sectional studies (Al-Hazzaa 2014;Al-Hazzaa et al 2012;Araujo et al 2012;Awad et al 2013;Bawazeer et al 2009;Bel et al 2013;Berentzen et al 2014;Butte et al 2007;Chaput et al 2011Chaput et al , 2014Calamaro et al 2010;Colley et al 2012;Culnan et al 2013;Danielsen et al 2010;de Jong et al 2012;Do et al 2013;Ekstedt et al 2013;Eisenmann et al 2006;Garaulet et al 2011;Guo et al 2012;Gupta et al 2002;Hense et al 2011;Hiscock et al 2011;Hjorth et al 2014aHjorth et al , 2014bHuang et al 2010;Katzmarzyk et al 2015;Knutson 2005;Knutson and Lauderdale 2007;Kong et al 2011;Kuciene and Dulskiene 2014;Lee and Park 2014;Liou et al 2010;Lowry et al 2012;Magee et al 2013a;Martinez-Gomez et al 2011;Meldrum and Restivo 2014;Morley et al 2012;Martinez et al 2014;Ozturk et al 2009;Padez et al 2009;Pallesen et al 2011;Park 2011…”
Section: Harms/injuriesmentioning
confidence: 99%